Effects of polyemitter crystal structure on the gain of a double poly bipolar transistor - Leow, Yong Faitt. (2008)
It was demonstrated that the common emitter current gain of bipolar transistors could be improved by replacing the emitter metal contact by a highly doped polysilicon layer. A number of works, both theoretical and experimental, investigating this effect, have been published. In all these studies, the analysis was done on the actual emitter structure of the bipolar transistor consisting of a thin (-2000A) heavily doped monocrystalline emitter region contacted by a heavily doped polysilicon layer about 2000A thick. The analysis of such a structure is difficult due to uncertainties in the bulk material properties and a poor understanding of the interface between the polysilicon and the single-crystal silicon layer. These uncertainties are further complicated by the presence of the grain boundaries in the polysilicon. Thus numerous assumptions are required to establish a minority-carrier transport model in the polysilicon contact.